An evaluation of TUPAD as a social protetion program for the indigents of San Jose Del Monte, Bulacan - Macasaet, Jules Hyacinth; Marte, Cris Laurence
This study investigated the Tulong Panghanapbuhay sa Ating Disadvantaged Workers (TUPAD) as a Social Protection Program for the indigent San Jose del Monte, Bulacan residents. The study aimed to: (1) describe how the PESO implements and monitors TUPAD in SJDM; (2) describe how TUPAD contributes to the capacity of the beneficiaries to meet their needs for health, education, and resource access; (3) identify the problems faced by the PESO and the TUPAD beneficiaries; (4) evaluate how effective TUPAD is in ensuring fair access, financial relief, and skill development opportunities for its beneficiaries, and (5) assess how effectively the program serves as an emergency employment initiative for disadvantaged workers. The study used Amartya Sen's Human Development Theory, specifically the Capability Approach, as its framework. Data were gathered through face-to-face interviews with the implementing agency and beneficiaries and a focus group discussion for monitoring coordinators. The study found that PESO administers the program in accordance with Department Order No. 239 s. 2023, and the monitoring assisted by Barangay Training and Employment Coordinators. However, several problems hinder the program's effectiveness including non-compliance with some training due to costs, ineffective beneficiary selection, delays in payments, repeated beneficiaries, over-reliance on TUPAD payouts, and lack of long-term employment opportunities. Regarding capabilities, TUPAD moderately alleviates financial stress and access to resources. However, while the program has increased interest in education, challenges remain in long-term employability and skills development. The study concludes that while TUPAD is an effective emergency employment program, with improved income based on poverty threshold analysis where TUPAD wages last from one week to one month-- it falls short in providing beneficiaries with long=term economic stability and capability enhancement. The study recommends the following: convergence of social protection programs, redefining the beneficiaries of TUPAD, digitalization of the database, and improvement of information dissemination on training.